On the Initial Value Problems for Caputo-Type Generalized Proportional Vector-Order Fractional Differential Equations - Mohamed I. Abbas; Snezhana Hristova (Mathematics, 2021)
A generalized proportional vector-order fractional derivative in the Caputo sense is defined and studied. Two types of existence results for the mild solutions of the initial value problem for nonlinear Caputo-type generalized proportional vector-order fractional differential equations are obtained. With the aid of the Leray–Schauder nonlinear alternative and the Banach contraction principle, the main results are established. In the case of a local Lipschitz right hand side part function, the existence of a bounded mild solution is proved. Some examples illustrating the main results are provided.